TEACHER OF PRIMARY EDUCATION IN INTERACTIVE ENVIRONMENT - EXAMPLES OF "BEST PRACTICE" - NEMCOVA, Jana (Trends in education, 2018)
Primary education teacher is considered to be irreplaceable and key element in the educational process, it is therefore important to gain his / her opinions, experiences and attitudes towards the use of interactive technologies in his / her work. The paper offers a look to examples of "best practice" related to the use of interactive technologies by teachers in primary education. The research part has a qualitative character, the design of a case study of primary education teachers.
Keywords: interactive technologies; teacher; examplest of "best practice"; primary education; case study